Genetic–epigenetic interaction modulates µ-opioid receptor regulation - Oertel, Bruno G.; Doehring, Alexandra; Roskam, Bianca; Kettner, Mattias; Hackmann, Nadja; Ferreirós, Nerea; Schmidt, Peter H.; Lötsch, Jörn (Human molecular genetics, 2012)
Genetic and epigenetic mechanisms play important roles in protein expression, although at different levels. Genetic variations can alter CpG sites and thus influence the epigenetic regulation of mRNA expression, providing an increasingly recognized mechanism of functional consequences of genetic polymorphisms. One of those genetic effects is the association of reduced μ-opioid receptor expression with the functional genetic variant N40D (OPRM1 118A>G, rs1799971) that causes an amino acid exchange in the extracellular terminal of the μ-opioid receptor. We report that the nucleotide exchange at gene position +118 introduces a new CpG-methylation site into the OPRM1 DNA at position +117. This leads to an enhanced methylation of the OPRM1 DNA at this site and downstream. This epigenetic mechanism impedes μ-opioid receptor upregulation in brain tissue of Caucasian chronic opiate addicts, assessed postmortem. While in wild-type subjects, a reduced signalling efficiency associated with chronic heroin exposure was compensated by an increased receptor density, this upregulation was absent in carriers of the 118G receptor variant due to a diminished OPRM1 mRNA transcription. Thus, the OPRM1 118A>G SNP variant not only reduces µ-opioid receptor signalling efficiency, but, by a genetic-epigenetic interaction, reduces opioid receptor expression and therefore, depletes the opioid system of a compensatory reaction to chronic exposure. This demonstrates that a change in the genotype can cause a change in the epigenotype with major functional consequences.